Utilization of organic fertilisers a potential approaches for agronomic crops: a review - Dalorima, Tahir; Sakimin, Siti Zaharah; Mohd Shah, Ramisah (HORIZON e-Publishing Group, 2021)
Organic fertilisers are of biological origin and the amount of nutrients they produce varies greatly. Besides providing the essential macro and micro nutrients, they also provide an array of plant growth-promoting substances. Organic agronomy is a relatively recent technique of farming in developed countries. While several studies were conducted on the impact of organic fertilisers on soil properties and crop production, further research is needed to determine comparative results between organic fertilisers. This paper aims to review some of the influences and impacts of poultry manure, cow dung, goat manure, vermicomposter and seaweed extracts. Much-needed characteristics of numerous crops were enhanced with the appropriate application of these organic fertilisers. Organic fertilizer applications influences the increase of plant heights, vegetative growth, yields and yield attributes. The application of adequate fertilisers also influences the qualitative parameters and post-harvest traits of most crops. Selecting the best organic fertilisers at an optimal application rate that could be the best source of nutrient supplement in cultivating qualitative crops, is a gap that needs to bridge. Therefore, different application rates of the above organic fertilisers were also studied.